ICON-ART 1.0 - A new online-coupled model system from the global to regional scale - Rieger, D.; Bangert, M.; Bischoff-Gauss, I.; Förstner, J.; Lundgren, K.; Reinert, D.; Schröter, J.; Vogel, H.; Zängl, G.; Ruhnke, R.; Vogel, B. (Copernicus Publications, 2016)
We present the first stage of a new online-coupled global to regional-scale modeling framework for the simulation of the spatiotemporal evolution of aerosols and trace gases. The underlying meteorological model is the new nonhydrostatic model system ICON (ICOsahedral Nonhydrostatic) which allows a local grid refinement with two-way interactions between the grids. We develop the extension ART (Aerosol and Reactive Trace gases) with the goal of simulating interactions between trace substances and the state of the atmosphere. Within this paper, we present the basic equations and give an overview of the physical parameterizations as well as numerical methods we use. First applications of the new model system for trace gases, monodisperse particles and polydisperse particles are shown. The simulated distribution of two very short-lived substances (VSLS), bromoform (CHBr 3 ) and dibromomethane (CH 2 Br 2 ) reflecting the fast upward transport shows a good agreement with observations and previous model studies. Also, the shape of the simulated tropical profiles is well reproduced. As an example for the treatment of monodisperse particles we present the simulated ash plume of the Eyjafjallajökull eruption in April 2010. Here, a novel approach for the source function is applied. The pattern of the simulated distribution of volcanic ash particles shows a good agreement with previous studies. As an example for the treatment of a polydisperse aerosol, where number densities and mass concentrations are accounted for, we simulated the annual emissions of sea salt. We obtain a total emission flux of 26.0 Pg yr-1 and an emission flux of particles with diameter less than 10 μm of 7.36 Pg yr-1.